2007
DOI: 10.4049/jimmunol.178.4.2122
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Control of Dendritic Cell Function Contributes to Development of CD4+ T Cell Anergy

Abstract: There is increasing evidence that dendritic cell (DC) immunogenicity is not only positively regulated by ligands of pattern recognition receptors, but also negatively by signals that prevent DC activation and full functional maturation. Depending on their activation status, DCs can induce either immunity or tolerance. In this study, we provide molecular evidence that the transcription factor peroxisome proliferator-activated receptor γ (PPARγ) is a negative regulator of DC maturation and function. Sustained PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 43 publications
7
115
0
1
Order By: Relevance
“…Besides their involvement in the macrophage for antiinflammatory response, activated PPARs play an important role in the production of retinoic acid, which regulates dendritic cell function and maturation, and the induction of CD4 + T-cell anergy (Klotz et al, 2007;Szatmari et al, 2006;. While proinflammatory cytokines inhibit PPARγ activity, interleukin (IL)-4 stimulates PPARγ interaction with STAT6 to promote gene expression in macrophages and dendritic cells (Szanto et al, 2010).…”
Section: Ppars and Inflammationmentioning
confidence: 99%
“…Besides their involvement in the macrophage for antiinflammatory response, activated PPARs play an important role in the production of retinoic acid, which regulates dendritic cell function and maturation, and the induction of CD4 + T-cell anergy (Klotz et al, 2007;Szatmari et al, 2006;. While proinflammatory cytokines inhibit PPARγ activity, interleukin (IL)-4 stimulates PPARγ interaction with STAT6 to promote gene expression in macrophages and dendritic cells (Szanto et al, 2010).…”
Section: Ppars and Inflammationmentioning
confidence: 99%
“…Furthermore, PPAR-c via induction of retinoic acid synthesis induces CD1d expression in DCs resulting in NKT cell proliferation and possibly altered lipid presentation by CD1 molecules [164,165]. Absence of PPAR-c in DCs increases their immunogenicity [166]. LXR also alters DC phenotype by decreasing IL-12, increasing IL-10 secretion and blocking its T-cell stimulatory ability [167].…”
Section: Involvement Of Adaptive Immune Response In Atherogenesismentioning
confidence: 99%
“…Previously, we and others have shown that activation of PPAR␥ suppresses DC maturation (22,23). Sustained activation of PPAR␥ in DCs prevented LPS-induced up-regulation of costimulatory molecules and production of proinflammatory cytokines.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…Sustained activation of PPAR␥ in DCs prevented LPS-induced up-regulation of costimulatory molecules and production of proinflammatory cytokines. In consequence, decreased signaling via signals 2 and 3 resulted in severely impaired priming of CD4 ϩ T cells by PPAR␥-activated DCs both in vitro and in vivo (23).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
See 1 more Smart Citation